2006
DOI: 10.1001/archinte.166.12.1269
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Comparison of Stroke Prevention Treatments in Individuals With Nonrheumatic Atrial Fibrillation

Abstract: A lower rate of ischemic stroke and a higher rate of major bleeding episodes were found to be associated with oral anticoagulants compared with aspirin, and both anticoagulants and aspirin were found to be associated with a reduction in the rate of stroke compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 39 publications
0
89
0
1
Order By: Relevance
“…Guidelines recommend warfarin therapy to decrease this risk [1]. Warfarin creates a 60-70% reduction of risk when compared to no treatment [4] and a 30-40% reduction when compared to aspirin [5]. More recently, left-atrial occlusion devices were proven noninferior to OAC therapy with warfarin and aspirin, although at the expense of higher periprocedural adverse events [6,7]; hence, the updated ESC guidelines consider it reasonable to use these devices for patients with a high risk of stroke and contraindications for long-term OAC [8].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend warfarin therapy to decrease this risk [1]. Warfarin creates a 60-70% reduction of risk when compared to no treatment [4] and a 30-40% reduction when compared to aspirin [5]. More recently, left-atrial occlusion devices were proven noninferior to OAC therapy with warfarin and aspirin, although at the expense of higher periprocedural adverse events [6,7]; hence, the updated ESC guidelines consider it reasonable to use these devices for patients with a high risk of stroke and contraindications for long-term OAC [8].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Roskell et al 33 conducted indirect comparisons and network meta-analyses of all pharmacological agents as compared with dabigatran. They suggested that dabigatran reduced stroke, systemic embolism, and mortality versus warfarin as well as antiplatelet agents and placebo.…”
Section: Commentmentioning
confidence: 99%
“…However, many perceive such a trial to be unethical in light of the overwhelming efficacy of the available Watchman trials. The yearly incidence of atrial fibrillation-mediated stroke without oral anticoagulation is well documented in excess of 5% in the both the numerous trials comparing warfarin with aspirin or no therapy 39 as well as the large stroke trials that have validated the CHADS and CHA 2 DS 2 -VASc scoring systems. 19,20 The long-term yearly The European Society of Cardiology (ESC) therefore seems justified in suggesting LAA closure be considered for patients with a high stroke risk and contraindications for long-term oral anticoagulation.…”
Section: Patient Selection For Laa Closure In 2014mentioning
confidence: 99%